2015
DOI: 10.1007/s00705-015-2585-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative molecular genetic analysis of simian and human HIV-1 integrase interactor INI1/SMARCB1/SNF5

Abstract: Human integrase interactor 1 (INI1/SMARCB1/SNF5) is a chromatin-remodeling molecule that binds to HIV-1 integrase and enhances proviral DNA integration. INI1 is also known as a tumor suppressor gene and has been found to be mutated in several aggressive tumors such as rhabdoid and lymphoid tumors. To study the function of simian INI1, we screened and cloned simian INI1 cDNA from B lymphoma cells of rhesus monkeys using RT-PCR. Sequence analysis showed 23 single nucleotide differences compared to the human orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…SMARCB1 is known to inhibit HIV replication in cell lines, possibly through the stabilization of pre-intregration complexes in non-reactive conformations (Das et al, 2009; Maroun et al, 2006; Pyeon et al, 2015). XRCC6 (Ku70) and other components of the NHEJ pathway, however, have an unclear role in the HIV lifecycle, though some results suggest a role in post-integration expression (Baekelandt et al, 2000; Jeanson et al, 2002; Li et al, 2001; Manic et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…SMARCB1 is known to inhibit HIV replication in cell lines, possibly through the stabilization of pre-intregration complexes in non-reactive conformations (Das et al, 2009; Maroun et al, 2006; Pyeon et al, 2015). XRCC6 (Ku70) and other components of the NHEJ pathway, however, have an unclear role in the HIV lifecycle, though some results suggest a role in post-integration expression (Baekelandt et al, 2000; Jeanson et al, 2002; Li et al, 2001; Manic et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, we particularly focused on Smarcb1, a sub-hub gene encoding an SWI/SNF-related matrix-associated actin-dependent regulator. It has seven isoforms in mouse and two in human, and this gene was previously reported to be related to chromatin remodeling [30][31][32]. Exon counts showed that most of the AS events occurred at exons 7-9,13-27, and 23-27, the latter of which correspond to the 3′ end of the CDS of SMARCB1 (Fig.…”
Section: Alternative Splicing At the Two-cell Stagementioning
confidence: 86%
“…The functions of these two isoforms have not been characterized, but one paper reported that the longer isoform seems to be more common in no‐fetal tissues while a shorter form is more prevalent in fetal tissues 91 . Interestingly, this two‐isoform pattern is also observed among humans, mice, and simian 92 . Moreover, the SFH1 in Saccharomyces cerevisiae , SNR1 in Drosophilia , SNF5 in Caenorhabditis elegans , and yeast counterparts have three highly conserved regions 89 .…”
Section: Mechanisms Of Mutated Swi/snf Complex In Tumorigenesismentioning
confidence: 99%
“… 91 Interestingly, this two‐isoform pattern is also observed among humans, mice, and simian. 92 Moreover, the SFH1 in Saccharomyces cerevisiae , SNR1 in Drosophilia , SNF5 in Caenorhabditis elegans , and yeast counterparts have three highly conserved regions. 89 Two of the three conserved regions are imperfect repeat motifs, Repeat 1(amino acids 186–245) and Repeat 2 (amino acids 259–319) (Figure 2B ).…”
Section: Mechanisms Of Mutated Swi / Snf...mentioning
confidence: 99%